An assessment of the technical constraints affecting rubber smallholders production capacity in Negeri Sembilan / Fazidah Rosli - Rosli, Fazidah (2012)
Malaysia's agricultural sector mainly dominated by different crops which comprises of oil palm, rubber and cocoa. From the statistics recorded, the average yield obtained from the rubber smallholders are very low that is 1,350 kg/ha/yr compared to the national average of 2, 000 kg/ha/yr. The objectives of this study are to assess the technical constraints faced by rubber smallholders in Negeri Sembilan and how the technical constraints affect their productions capacity. This study found that most of the rubber smallholders towards the study area gain more or less 1,350 to I, 400 kg/ha/year. Most of them were still produced below the national average eventhough RlSDA has provided them guidance and technologies. The main constraints faced by smallholders was they refused to adopt the technologies and most of them could not afford to purchase the technologies.